Are There Early Risk Markers for Pedophilia? A Nationwide Case-Control Study of Child Sexual Exploitation Material Offenders. Issue 2 (12th February 2019) - Babchishin, Kelly M.; Seto, Michael C.; Fazel, Seena; Långström, Niklas
Abstract : Although prior research suggests associations between parental characteristics and later sexual offending in offspring, possible links between early pregnancy-related factors and sexual offending remain unclear. Early risk markers unique to sexual offending, however, may be more prominent among sexual offenders with atypical sexual interests, such as individuals involved with child sexual exploitation material (CSEM; also referred to as child pornography). We examined the prospective association between parental and pregnancy-related risk markers and a behavioral indicator of pedophilic interest, CSEM offending. All 655 men born in Sweden and convicted of CSEM offending between 1988 to 2009 were matched 1:5 on sex, birth year, and county of birth in Sweden to 3, 928 controls without sexual or nonsexual violent convictions. Paternal age (adjusted odds ratio [AOR] = 1.3, 95% confidence interval [CI] [1.1, 1.7]), parental education (AOR = 0.8, 95% CI [0.6, 0.9]), parental violent criminality (AOR = 2.9, 95% CI [2.2, 3.8]), number of older brothers (AOR = 0.8, 95% CI [0.6, 0.9] per brother), and congenital malformations (AOR = 1.7, 95% CI [1.2, 2.4]) all independently predicted CSEM convictions. This large-scale, nationwide study suggests parental risk markers for CSEM offending. We did not, however, find convincing evidence for pregnancy-related risk markers, with the exception of congenital malformations and having fewer older brothers.